(3GdJNWjW eY MQjI GdShbs - (3YdGe(B, (3SYO Wgs ((3GdbGgQIs (3OGQ WHjI ddfTQ hGdJhRjY hGdJLgjRGJ GdYdejIs, 2003)
(3jYJHQ gPG GdcJGH (B((3GdJNWjW eY MQjI GdShb(B" (3fehPLkG jMJPi Hg aj LejY GdHdOGf GdYQHjI cbjeI YdejI KGHJI aj YGde GdJNWjW, ehVMkG GdCgejI GdHGdZI ddJNWjW aj HfGA GdeLJeY GdCeKd ddJbOe ef NdGd JWHjbgG Ydi CQV GdhGbY eDcOkG Ydi eJGHYI JfajP YedjI GdJNWjW dJchf aj ChL GdYWGA(B. (3LOjQ HGdPcQ Cf gPG GdcJGH ef Cge GdcJH GdGbJUGOjI GdJj jgah dgG GdegJehf hGdHGMKhf GdGbJUGOjhf(B...(3JLQHI GdJNWjW aj eUQ ; gjcd GdfXGe GdJNWjWj GddGeQcRj ; GdJJNWjW GdJCTjQj ddGSJKeGQ ; OQGSI GdShb hJbOjQ GdWdH QcjRI CSGSjI aj GYOGO NWI ; GdJNWjW GdbWGYj (B-(3GYOGO hJfajP NWI bWGY GdRQGYJI ceKGd ddNWII GdbWGYjI ; GdJNWjW Ydi eSJhi GdhMOI hGdeTQhY ; GdeJGHYI hGdQbGHI GdJNWjW HGdeTGQcI (B- (3GdLhGfH GdJWHjbjI ddJLQHIs
Keywords: (3GdJNWjWs; (3GdShbs